Physiological Features of Pennisetum Purpureum or Panicum Maximum Consumption in Guinea Pigs (Cavia Porcellus) - Emile Miégoué; Fernand Tendonkeng; Nathalie Mweugang Ngouopo; Loïc Arnauld Mba Tene; Paulette Ntsafack; Etienne Tedonkeng Pamo (Journal of Zoological Research, 2018)
Guinea pig diet is essentially based on the use of grasses associated with protein sources. Then, in to improve the herbivores nutrition, the evaluation of intake and In vivo digestibility of Pennisetum purpureum or Panicum maximum in guinea pigs (Cavia porcellus) was carried out in January 2017 at the University of Dschang research and experimental farm and animal production and nutrition laboratory. 20 adult animals of local breed on average weight 450 ± 50g and aged about 5 months were used. They were organized into two batches of 10 animals each (5 males and 5 females). The first batch received 250g of fresh matter of Pennisetum purpureum + 60g concentrate/animal/day, while the second received the same treatment with Panicum maximum as grasses. Leftover and animals were weighed every morning before food distributions, and drinking water containing vitamin C was served ad libitum. According to the results, the highest ingestion was obtained with Panicum maximum. However, the digestibility different nutrients was comparable between treatments; nevertheless, males fed on P. maximum digested crude cellulose (63.78%) better than males fed on P. purpureum (51.17%). With regard to the variation of the bacterial rate of the caecal flora, enterobacteria of animals fed P. maximum was high (11.20 CFU/ml) compared to those of the animals receiving P. purpureum (7.27 CFU/ml), although regardless of the treatment, the level of lactobacilli was higher than that of enterobacteria. In view of the results obtained, these grasses can be alternatively used in feeding guinea pigs.
Keywords: Grasses